Routing cancer immunology and immunotherapy from the lab to the clinic 4–5 th March 2014, Center for Applied Medical Research and University Clinic, Pamplona, Spain - Aznar, M Ángela (BioMed Central, 2014)
New approaches to generate effective anticancer responses by either inducing immune responses or inhibiting immunosuppression are under development to improve efficacy in patients. On March 4-5(th), 2014, a symposium was held in Pamplona, Spain, to report the new strategies showing preclinical and clinical results regarding translational research efforts on the topic. Participants interacted through oral presentations of 15 speakers and further discussions on topics that included novel therapeutic agents for cancer immunotherapy, viral vectors and interferon-based approaches, experimental tumor imaging and immunostimulatory monoclonal antibodies. Promising agents to target cancer cells and therapeutic approaches that are under translation from bench to patients were presented.